Ag2S‑Sensitized NiO–ZnO Heterostructures with Enhanced Visible Light Photocatalytic Activity and Acetone Sensing Property - Shafi, Adil; Ahmad, Nafees; Sultana, Saima; Sabir, Suhail; Khan, Mohammad Zain (ACS omega, 2019)
Visible light-driven Ag2S-grafted NiO–ZnO ternary nanocomposites are synthesized using a facile and cost-effective homogeneous precipitation method. The structural, morphological, and optical properties were extensively studied, confirming the formation of ternary nanocomposites. The surface area of the synthesized nanocomposites was calculated by electrochemical double-layer capacitance (C dl). Ternary Ag2S/NiO–ZnO nanocomposites showed excellent visible light photocatalytic property which increases further with the concentration of Ag2S. The maximum photocatalytic activity was shown by 8% Ag2S/NiO–ZnO with a RhB degradation efficiency of 95%. Hydroxyl and superoxide radicals were found to be dominant species for photodegradation of RhB, confirmed by scavenging experiments. It is noteworthy that the recycling experiments demonstrated high stability and recyclable nature of the photocatalyst. Moreover, the electrochemical results indicated that the prepared nanocomposite exhibits remarkable activity toward detection of acetone. The fabricated nanocomposite sensor showed high sensitivity (4.0764 μA mmol L–1 cm–2) and a lower detection limit (0.06 mmol L–1) for the detection of acetone. The enhanced photocatalytic and the sensing property of Ag2S/NiO–ZnO can be attributed to the synergistic effects of strong visible light absorption, excellent charge separation, and remarkable surface properties.